(untitled) (Annals of Medical Research, 2022)
Aim: To evaluate is the relationship of enlarged main pulmonary artery (mPA) diameter in COVID-19 with disease severity and early term prognosis by using computed tomography severity score (CTSS). Materials and Methods: 906 of 1650 COVID-19 patients with chest computed tomography (CT) included in the study. The patient groups were divided in two as short (≤7 day) and long (>7 day) hospitalization according to the length of hospital stay. The patients who were admitted to the intensive care unit (ICU) and those who died were also recorded. We assessed CTSS and PA diameter on CT images. Results: 540 (60%) patients had pneumonia. 291 (54%) of them were found to have pure ground glass opacity (GGO), 168 (31%) of them were found to have both GGO and consolidation, 60 (11%) of them were found to have consolidation and 21 (4%) of them were found to have crazy paving pattern. There was a significant correlation between PA diameter and hospitalization time (r:0.339; p<0.001), intensive care unit (ICU) need and mortality (r:0.398, 0.326; respectively; p<0.001). There was a significant correlation between PA increase and CTTS increase (r:0.226; p=0.002). The area under the curve of the mPA in predicting patient mortality was 0.805 (95% CI:0.695–0.915). The best cut-off value of mPA was taken as 28,4 sensitivity and specificity was found 78.9%, 74.5% respectively. CTSS of the cases who died because of COVID-19 were significantly higher (p=0.023). The area under the ROC curve of CTSS in predicting patient mortality was 0.668 (95% CI:0.554-0.781). The best cut off value of CTSS was taken as 13 sensitivity and specificity was found 57.8%, 80.9% respectively. Conclusion: mPA diameter increase is associated with poor prognosis including long term hospitalization, ICU hospitalization and mortality in COVID-19 cases.